Alterations of Static and Dynamic Functional Connectivity of the Nucleus Accumbens in Patients With Major Depressive Disorder - Zhou, Bingqian; Chen, Yuan; Zheng, Ruiping; Jiang, Yu; Li, Shuying; Wei, Yarui; Zhang, MengZhe; Gao, XinYu; Wen, Baohong; Han, Shaoqiang; Cheng, Jingliang (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) is associated with dysfunction of the reward system. As an important node in reward system, the resting-state functional connectivity of the nucleus accumbens (NAc) is related to etiology of MDD. However, an increasing number of recent studies propose that brain activity is dynamic over time, no study to date has examined whether the NAc dynamic functional connectivity (DFC) is changed in MDD patients. Moreover, it remains unclear whether clinical characteristics of MDD patients affect the NAc-based RSFC and DFC. Methods: A total of 220 MDD patients and 159 healthy controls (HCs), group-matched for age, sex and education level, underwent resting-state functional magnetic resonance imagining (rs-fMRI) scans. Seed-based RSFC and DFC of the NAc were conducted. Two sample t test was peformed to altered RSFC/DFC of NAc. In addition, we examined the asccociation between altered RSFC/DFC and clinical symptoms using pearson correlation. Finally, we examined the impact of clinical characteristics on the NAc RSFC and DFC. Results: Compared with the HCs, MDD patients show reduced the NAc-based RSFC with the dorsolateral prefrontal cortex (DLPFC), hippocampus, middle temporal gyrus (MTG), inferior temporal gyrus (ITG), precuneus and insula, and MDD patients show reduced the NAc-based DFC with the DLPFC, ventromedial prefrontal cortex (VMPFC), ventrolateral prefrontal cortex (VLPFC), MTG, ITG, and insula. MDD severity was associated with RSFC between the NAc and precentral gyrus (r=0.288, p=0.002, uncorrected) and insula (r=0.272, p=0.003, uncorrected). Conclusion: This study demonstrates abnormal RSFC and DFC between the NAc and distributed cerebral regions in MDD patients, characterized by decreased RSFC and DFC of the NAc connecting with the reward, executive, default-mode and salience network. Our results expand previous descriptions of the NAc RSFC abnormalities in MDD, and the altered in the RSFC/DFC may reflect disrupted function of the NAc.